The epidemiology and management of chronic osteomyelitis in pediatrics – A systematic review - Joan L. Robinson; Deema Gashgarey; Nourah Alruqaie; Liz Dennett; M. Elizabeth Pedersen (PLoS ONE, 2025)
Objectives Infection leading to necrosis of any bone can lead to chronic osteomyelitis (CO), sometimes resulting in permanent orthopedic sequelae. There are no published guidelines on the optimal management of adult or pediatric CO The objective of this study was to analyze published evidence for the epidemiology and management of pediatric CO. Methods Inclusion criteria were studies of any design (minimum 2 patients) in any language that included patients with CO up to 17 years of age and described the epidemiology or management of CO. Ovid Medline(R) ALL, Embase (via Ovid), CINAHL Plus with Full Text (via EBSCOhost) and Scopus were screened Jan 1, 1989 to Feb 13, 2025. Quality assessment was based on the degree of bias if one were to use that study to make decisions about management of CO. Studies were divided into those from middle-high and high-income countries versus studies from lower income countries. Data were extracted on demographics, biomarkers, pathogens, treatments offered, recurrences and orthopedic sequelae. Results There were 41 included studies – 26 from middle-high- and high-income countries (904 cases total) and 15 from lower income countries (975 cases total). All were observational and only 19 of the 41 studies reported 7 or 8 of the 8 items deemed essential to make decisions about management of CO. Definitions of CO varied markedly. Analyzing the 17 studies that included a minimum of 10 consecutive cases, 627 of 1073 cases (58%) occurred in males. In these 17 studies, the tibia or femur accounted for 630 of 934 cases (67%). In 212 of 287 cases (74%) with a single pathogen reported, that pathogen was Staphylococcus aureus . There were no apparent differences in sex, bones involved or pathogens by country income level. Most cases (with the notable exception of those in recent case series from the United States) were managed with debridement. This was typically followed by sequential intravenous/per os (IV/ PO) antibiotics with almost no patients managed with PO antibiotics alone. Twelve case series reported use of local antibiotic delivery in addition to systemic antibiotics, but none of these studies had a control group. Studies were too heterogeneous in design to allow for data to be directly compared or combined. However, there was no obvious relationship between the route or duration of antimicrobials and the incidence of recurrences or orthopedic sequalae. Conclusion There is a great need for high quality studies of all aspects of diagnosis and treatment of CO. Empiric coverage should target S. aureus . The evidence is poor quality, but there is no evidence that prolonged courses of antibiotics prevent recurrences.